2023
DOI: 10.1002/advs.202205890
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle Exsolution from Nanoporous Perovskites for Highly Active and Stable Catalysts

Abstract: Nanoporosity is clearly beneficial for the performance of heterogeneous catalysts. Although exsolution is a modern method to design innovative catalysts, thus far it is predominantly studied for sintered matrices. A quantitative description of the exsolution of Ni nanoparticles from nanoporous perovskite oxides and their effective application in the biogas dry reforming is here presented. The exsolution process is studied between 500 and 900 °C in nanoporous and sintered La 0.52 Sr 0.28 Ti 0.94 Ni 0.06 O 3±𝜹 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 82 publications
3
7
0
Order By: Relevance
“…This behavior is in accordance with the lower surface Ni content estimated by H 2 -TPR. Furthermore, this confirms the sintering of exsolved Ni NPs during the reduction step at 800 °C, consistent with recent observations of Rudolph et al 31 Their findings suggest that at high reduction temperatures, Ni atoms rapidly diffuse to existing nuclei on the surface, promoting the growth of Ni NPs instead of forming new smaller ones. A prolonged reduction time of 800 °C clearly promotes the growth of Ni NPs.…”
Section: Catalytic Activity Measurementssupporting
confidence: 92%
“…This behavior is in accordance with the lower surface Ni content estimated by H 2 -TPR. Furthermore, this confirms the sintering of exsolved Ni NPs during the reduction step at 800 °C, consistent with recent observations of Rudolph et al 31 Their findings suggest that at high reduction temperatures, Ni atoms rapidly diffuse to existing nuclei on the surface, promoting the growth of Ni NPs instead of forming new smaller ones. A prolonged reduction time of 800 °C clearly promotes the growth of Ni NPs.…”
Section: Catalytic Activity Measurementssupporting
confidence: 92%
“…The total cycle number in the present CL-DRM over Ni/WO 3 (10)/ZrO 2 is the highest among the previously reported CL-DRM systems (Table S2). In another conventional DRM experiment performed at 750 °C, 1% CH 4 /1% CO 2 /He continuously flowed over Ni/WO 3 (10)/ZrO 2 . Initially, more than 99% of CH 4 and CO 2 were converted in conventional DRM (squares in Figure ); however, the conversions monotonically decreased with time.…”
Section: Resultsmentioning
confidence: 99%
“…The excessive emission of greenhouse gases (GHG) such as methane (CH 4 ) and carbon dioxide (CO 2 ) has become a global environmental problem. , CH 4 and CO 2 valorization, a favorable route to reduce GHG emissions, have been a subject of intense research. Dry reforming of methane (DRM) is a promising catalytic reaction that can convert CH 4 and CO 2 to syngas (CO and H 2 ). , Although several efficient and durable catalyst systems for DRM have been developed recently, most reported catalyst systems suffer from certain drawbacks, such as catalyst deactivation due to coke deposition and undesired CO 2 reduction by the generated H 2 . Chemical looping dry reforming of methane (CL-DRM) has received considerable attention as an alternative technology to circumvent these drawbacks.…”
Section: Introductionmentioning
confidence: 99%
“…Using TPD and XANES analyses for La 0.52 Sr 0.28 Ti 0.94 Ni 0.06 O 3± δ , it has been experimentally confirmed that a faster and greater release of oxygen in the nanoporous material results in twice as much Ni exsolution as in the sintered ceramics. 259 The high rate of oxygen exsolution also increases the nucleation kinetics of nanoparticles in SrTi 0.65 Fe 0.35 O 3− δ oxide, 260 Fig. 12A.…”
Section: Characterization Of Surface Segregation: Approachesmentioning
confidence: 97%